International Studies in the Global Information Age. - Simmons, Beth A. (International Studies Quarterly, 2011)
The Global Information Age poses new and interesting questions for the study of international affairs. This Presidential Address surveys recent developments in commercialized and globalized information technologies that have and will continue to impact political and social relationships around the world. These new technologies affect power relationships among states, as well between states and civil society. They also present possibilities for new forms of global accountability and participation in governance. Finally, a range of technologies offer new and powerful ways to collect data for our research that allow us to ask new questions. President Simmons concludes as a result that exploratory empirical research is more enticing than ever before, but cautions that we should never think we can outsource the hard job of thinking to the very technologies that make innovative research possible in the first place.